The Effectiveness of the 8w's Model of Investigation in ‎Developing Emotional ‎Regulation Skills Among First-Year ‎Students in the Department of Sociology - Sarab Mahmoud Kareem (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: The current study aimed to identify the effectiveness of the 8w's model ‎of investigation in developing emotional regulation skills in the subject of ‎philosophy for the academic year 2023/2024. Methodology: A single-group ‎experimental design with a pre and post-test was adopted, which included (76) ‎male and female students who were intentionally selected from the Department ‎of Sociology/ College of Arts, Tikrit University. In addition, the researcher ‎created a test of emotional regulation skills consisting of (18) situations, for ‎each skill (3) situations. The test was judged by a group of experts to ‎demonstrate its validity. Some psychometric properties of the test were also ‎extracted to ensure its validity and reliability. It was then submitted to the ‎research sample before and after according to the plan prepared by the research. ‎Results: The data were statistically analyzed using the statistical package for ‎Social Sciences (SPSS). The results of the statistical analyses indicated that the ‎eight-point model has a statistically significant effectiveness in developing ‎emotional regulation skills. Conclusions: Based on the findings of this study, it ‎can be concluded that the use of teaching methods, its techniques, and a variety ‎of strategies leads to better outcomes in raising students' levels in the abstract ‎subject of philosophy. Furthermore, the eight-point model has statistically ‎succeeded in yielded good results for developing students' emotional regulation ‎skills ‎